Fiscal Limits, External Debt, and Fiscal Policy in Developing Countries - Bi, Huixin (IMF Working Papers; Working Paper ;, 2014)
This paper studies fiscal policy effects in developing countries with external debt and sovereign default risks. State-dependent distributions of fiscal limits are simulated based on macroeconomic uncertainty and fiscal policy specifications. The analysis shows that expected future revenue plays an important role in the low fiscal limits of developing countries, relative to those of developed countries. External debt carries additional risks since large devaluation of the real exchange rate can suddenly raise default probabilities. Consistent with majority views, fiscal consolidations are counterproductive in the short and medium runs. When an economy approaches its fiscal limits, government spending can be less expansionary than in a low-debt state. As more revenue is required to service debt in a high-debt state, higher tax rates raise the economic cost of increasing consumption, reducing the fiscal multiplier.